Ablation-resistant transpiration cooling coating and method for preparing ablation-resistant transpiration cooling coating using high-speed laser cladding self-transportation effect
Patent Information
- Application Number
- CN202311760381.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-20
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-12-20
AI Technical Summary
[0005]本发明的目的是为了解决现有超高温陶瓷耐烧蚀涂层,采用化学气相沉积工艺制备的涂层厚度仅为几微米,采用等离子喷涂工艺制备的涂层存在大量孔洞等问题,而提供一种利用高速激光熔覆自传质效应制备耐烧蚀蒸腾冷却涂层及其制备方法
[0012] The low-melting-point metal matrix is made of aluminum alloy or copper alloy.
Smart Images

Figure CN117721460B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite protective coatings, specifically relating to a method for preparing an ablation-resistant coating that exhibits an evaporative cooling effect in an ablation environment. Background Technology
[0002] In 2018, the world's first all-aluminum aero-engine was developed at Novosibirsk Polytechnic University. Compared to traditional aero-engines, this all-aluminum engine reduces weight and fuel consumption by 40% and 15% respectively, while increasing horsepower by 40. Currently, due to the material properties of aluminum alloys, this engine is only used on the Yak-52 trainer aircraft. It is well known that military aero-engines must withstand temperatures exceeding 2000K and face harsh ablation environments; such demanding service conditions are devastating to aluminum alloy materials. Therefore, the development of ablation-resistant coatings on aluminum alloy surfaces is crucial for further advancing the development of all-aluminum aero-engines.
[0003] W-Cu alloys, widely used in the throats and nose cones of rocket engine nozzles, are alloys with good ablation resistance. In ablation environments, the higher melting point of W provides good ablation resistance, while the lower melting point of Cu can reduce the temperature of the ablation surface through evaporation-cooling effects, thereby improving the material's ablation resistance. Combining this material with evaporation-cooling effects with surface coating technology has proven to be a good means of improving the ablation resistance of parts. For example, Zhang et al. prepared Ir and Ir-Al coatings on graphite surfaces using chemical vapor deposition and electrodeposition methods. The effect of Al addition on the ablation resistance of the Ir coating was investigated in a plasma wind tunnel environment. (The text abruptly ends here, so the translation stops as well.) 2 The addition of Al reduced the temperature of the ablation surface of the coating by 1164℃, significantly improving its ablation resistance (Surface and Coatings Technology, 2019, 358, 371-377). Ultra-high temperature ceramics, with melting points above 3000℃, are considered among the few materials capable of operating in environments above 2000℃. Numerous studies have shown that preparing ultra-high temperature ceramic coatings or introducing them into existing coating systems can increase the overall melting point of the coating, thereby obtaining coatings with better ablation resistance. Therefore, ultra-high temperature ceramics can be used as the ablation-resistant phase in ablation-resistant evaporative cooling coating.
[0004] Currently, the preparation technologies for ultra-high temperature ceramic ablation-resistant coatings mainly focus on chemical vapor deposition (CVD) and plasma spraying. The former produces coatings only a few micrometers thick, which is insufficient for prolonged ablation environments. The latter, plasma spraying, produces coatings composed of unmelted or semi-melted particles, resulting in numerous pores. In high-temperature ablation environments, this accelerates oxygen diffusion and coating peeling, ultimately reducing the coating's service life. Furthermore, the interface between the plasma-sprayed coating and the substrate is a mechanical bond formed by the collision of high-speed particles with the substrate. This interface is highly susceptible to coating detachment in high-temperature ablation environments due to mismatches in thermal expansion coefficients between the coating and the substrate. Therefore, there is an urgent need to explore new surface coating technologies to address these issues. Summary of the Invention
[0005] The purpose of this invention is to solve the problems of existing ultra-high temperature ceramic ablation-resistant coatings, such as coating thickness of only a few micrometers prepared by chemical vapor deposition and coatings with a large number of pores prepared by plasma spraying. The invention provides a method for preparing an ablation-resistant evaporative cooling coating using the self-mass transfer effect of high-speed laser cladding.
[0006] The ablation-resistant evaporative cooling coating of this invention is prepared by a high-speed laser cladding process. The cladding nozzle sprays silicon carbide-ultra-high temperature ceramic composite powder, and the laser beam simultaneously irradiates the silicon carbide-ultra-high temperature ceramic composite powder and the surface of a low-melting-point metal substrate, forming a coating containing an ablation-resistant phase and an evaporative cooling phase on the surface of the low-melting-point metal substrate. The ablation-resistant phase is the silicon carbide-ultra-high temperature ceramic composite material, and the evaporative cooling phase is the metal phase of the low-melting-point metal transferred to the coating through the self-mass transfer effect. The material of the low-melting-point metal substrate is an aluminum alloy or a copper alloy.
[0007] The ablation-resistant evaporative cooling coating of this invention comprises an ablation-resistant phase and an evaporative cooling phase. The ablation-resistant phase in the coating originates from the original silicon carbide-ultra-high temperature ceramic composite powder, while the evaporative cooling phase originates from a low-melting-point metal matrix. The low-melting-point metal matrix in the coating is transferred from the matrix to the coating through a self-mass transfer effect during the high-speed laser cladding process.
[0008] The present invention utilizes the self-mass transfer effect of high-speed laser cladding to prepare an ablation-resistant evaporation cooling coating, which is achieved through the following steps:
[0009] 1. Use #240~#300 sandpaper to polish the surface of the low melting point metal substrate, and then immerse the low melting point metal substrate in anhydrous ethanol for ultrasonic cleaning to obtain the cleaned metal substrate.
[0010] 2. Place the silicon carbide-ultra-high temperature ceramic composite powder in a drying oven and dry it at a temperature of 60-100℃. After sieving, the silicon carbide-ultra-high temperature ceramic composite powder with a particle size of 45-70μm is obtained.
[0011] 3. Load silicon carbide-ultra-high temperature ceramic composite powder into a powder feeding tank, adjust the focal points of the laser beam and the powder beam to coincide below the cladding nozzle, place the metal substrate to be clad 0.5-1.2mm below the focal point, control the laser power to be 2300-3300W, the cladding speed to be 90-150mm / s, the powder feeding rate to be 2.8-3.4g / min, the overlap rate to be 75%-90%, and the spot diameter to be 2-3mm. Perform high-speed laser cladding under the protection of local inert gas to form an ablation-resistant evaporation cooling coating on the surface of the low melting point metal substrate.
[0012] The low-melting-point metal matrix is made of aluminum alloy or copper alloy.
[0013] The ablation-resistant evaporative cooling coating prepared by this invention exhibits excellent metallurgical bonding at the interface with the substrate. The coating has a dense internal structure without obvious cracks or pores. The ablation-resistant silicon carbide-ultra-high temperature ceramic phase is uniformly distributed within the coating, while the evaporative-cooled substrate phase acts as the coating's framework.
[0014] This invention uses silicon carbide-ultra-high temperature ceramic composite powder as the raw powder for high-speed laser cladding, successfully introducing low-melting-point metals into the coating by utilizing the self-mass transfer effect of high-speed laser cladding. The coating forms a structure with both an ablation-resistant phase and a evaporating cooling phase. The prepared coating exhibits excellent ablation resistance at high heat flux densities. At 35.39 MW / m²... 2 After ablation at a heat flux density of 70.77 MW / m³ for 8 seconds, the surface morphology and color of the coating did not change significantly. 2 After ablation for 8 seconds at a heat flux density of 106.16 MW / m, the coating surface only showed a slight color change, and the ablation threshold of the coating was not reached. 2 At a heat flux density of 141.54 MW / m², the ablation threshold of the coating was reached after 8 seconds of ablation, and obvious ablation pits appeared on the coating surface. 2 Although larger ablation pits appeared in the coating after 8 seconds of ablation at the specified heat flux density, the coating was not completely depleted. The low-melting-point matrix phase transferred to the coating via the self-mass transfer effect of high-speed laser cladding exhibited a significant evaporative cooling effect during ablation. This not only increased the ablation threshold of the coating but also improved its performance even at a heat flux density of 141.54 MW / m³. 2 The coating was not depleted even after 8 seconds of ablation. In summary, the ablation-resistant evaporative cooling coating prepared by high-speed laser cladding exhibits excellent ablation resistance.
[0015] The ablation-resistant evaporative cooling coating prepared by this invention can be used to enhance the ablation resistance of low-melting-point metal parts. In high-temperature ablation environments, the evaporative cooling effect of the coating can significantly improve its ablation resistance and provide excellent protection to the substrate.
[0016] This invention proposes a method for preparing an ablation-resistant evaporative cooling coating using the self-mass transfer effect of high-speed laser cladding. Traditionally, the transfer of matrix elements in the coating via the self-mass transfer effect during high-speed laser cladding has been thought to only disrupt the original material composition of the coating, negatively impacting its performance. The self-mass transfer effect during high-speed laser cladding can be categorized as incomplete or complete, depending primarily on the selection of the high-speed laser cladding process parameters. In this invention, to ensure the uniform distribution of the low-melting-point metal matrix in the coating, the self-mass transfer effect should be controlled to be complete. This invention successfully incorporates the low-melting-point matrix phase transferred to the coating via the self-mass transfer effect as a crucial component of the coating, improving its ablation resistance. The degree of self-mass transfer and coating quality are optimized by adjusting the high-speed laser cladding process parameters. The coating exhibits excellent quality: free of internal defects such as pores and cracks; and a perfect metallurgical bond between the coating and the matrix at the interface. The phase composition of the coating also exhibits a structure of ablation-resistant phase plus a low-melting-point matrix phase. This invention successfully transforms the disadvantages of the self-mass transfer effect in high-speed laser cladding into advantages, preparing an ablation-resistant evaporative cooling coating with excellent performance. The method is simple, easy to implement, and produces coatings with superior performance. Attached Figure Description
[0017] Figure 1 The cross-sectional morphology of sample 1, a 6061 aluminum alloy surface clad with an ablation-resistant evaporation cooling coating, is shown in Example 1. Figure 1 (a) shows the macroscopic cross-sectional morphology. Figure 1 (b) shows the microscopic cross-sectional morphology;
[0018] Figure 2 for Figure 1 The surface morphology diagram of sample 1 shown is shown, in which, Figure 2 (a) shows the macroscopic surface morphology. Figure 2 (b) shows the microscopic surface morphology.
[0019] Figure 3 for Figure 1 The cross-sectional secondary electron micrograph and phase composition analysis of sample 1 shown are presented in the diagram. Figure 3 (a) shows the cross-sectional secondary electron microstructure of the coating; Figure 3 (b) is a diagram showing the phase composition analysis results of the coating;
[0020] Figure 4 for Figure 1 The surface morphology of sample 1 before and after ablation under different heat flux densities is shown; where Figure 4(a) and (a1) represent heat flux densities of 35.39 Mw / m³. 2 Surface morphology of the coating before and after ablation; Figure 4 (b) and (b1) represent heat flux densities of 70.77 Mw / m³. 2 Surface morphology of the coating before and after ablation; Figure 4 (c) and (c1) represent heat flux densities of 106.16 Mw / m³. 2 Surface morphology of the coating before and after ablation; Figure 4 (d) and (d1) represent heat flux densities of 141.54 Mw / m³. 2 Surface morphology of the coating before and after ablation;
[0021] Figure 5 This is a cross-sectional morphology diagram of sample 2, a 6061 aluminum alloy surface clad with an ablation-resistant evaporation cooling coating, in Example 2. Figure 5 (a) shows the macroscopic interface morphology. Figure 5 (b) shows the microscopic cross-sectional morphology;
[0022] Figure 6 This is a cross-sectional morphology diagram of sample 3, a 6061 aluminum alloy surface clad with an ablation-resistant evaporation cooling coating, in Example 3. Figure 6 (a) shows the macroscopic interface morphology. Figure 6 (b) shows the microscopic cross-sectional morphology. Detailed Implementation
[0023] Specific Implementation Method 1: In this implementation method, the ablation-resistant evaporative cooling coating is prepared using a high-speed laser cladding process. The cladding nozzle sprays silicon carbide-ultra-high temperature ceramic composite powder, and the laser beam simultaneously irradiates the silicon carbide-ultra-high temperature ceramic composite powder and the surface of a low-melting-point metal substrate, forming a coating containing an ablation-resistant phase and an evaporative cooling phase on the surface of the low-melting-point metal substrate. The ablation-resistant phase is the silicon carbide-ultra-high temperature ceramic composite material, and the evaporative cooling phase is the metal phase of the low-melting-point metal transferred to the coating through the self-mass transfer effect. The material of the low-melting-point metal substrate is an aluminum alloy or a copper alloy.
[0024] This embodiment of the ablation-resistant evaporative cooling coating includes an ablation-resistant phase and an evaporative cooling phase. The ablation-resistant phase in the coating originates from the original silicon carbide-ultra-high temperature ceramic composite powder, while the evaporative cooling phase originates from a low-melting-point metal matrix. The evaporative cooling phase in the coating is transferred from the matrix to the coating through the self-mass transfer effect during the high-speed laser cladding process. The matrix is a metal material with a low melting point, which can be transferred to the coating through the self-mass transfer effect during the high-speed laser cladding process. During the coating ablation process, the evaporative cooling effect reduces the temperature of the ablated surface, improving the coating's ablation resistance.
[0025] Specific Implementation Method Two: The difference between this implementation method and Specific Implementation Method One is that the coating thickness formed on the surface of the low melting point metal substrate is 300-450μm.
[0026] Specific Implementation Method 3: This implementation method for preparing an ablation-resistant evaporative cooling coating using the self-mass transfer effect of high-speed laser cladding is carried out according to the following steps:
[0027] 1. Use #240~#300 sandpaper to polish the surface of the low melting point metal substrate, and then immerse the low melting point metal substrate in anhydrous ethanol for ultrasonic cleaning to obtain the cleaned metal substrate.
[0028] 2. Place the silicon carbide-ultra-high temperature ceramic composite powder in a drying oven and dry it at a temperature of 60-100℃. After sieving, the silicon carbide-ultra-high temperature ceramic composite powder with a particle size of 45-70μm is obtained.
[0029] 3. Load silicon carbide-ultra-high temperature ceramic composite powder into a powder feeding tank, adjust the focal points of the laser beam and the powder beam to coincide below the cladding nozzle, place the metal substrate to be clad 0.5-1.2mm below the focal point, control the laser power to be 2300-3300W, the cladding speed to be 90-150mm / s, the powder feeding rate to be 2.8-3.4g / min, the overlap rate to be 75%-90%, and the spot diameter to be 2-3mm. Perform high-speed laser cladding under the protection of local inert gas to form an ablation-resistant evaporation cooling coating on the surface of the low melting point metal substrate.
[0030] The low-melting-point metal matrix is made of aluminum alloy or copper alloy.
[0031] In step three of this embodiment, before the high-speed laser cladding experiment begins, the focal points of the laser beam and the powder beam are adjusted to coincide below the high-speed laser cladding nozzle, and then the substrate surface to be clad is placed 0.5-1.2 mm below the two focal points.
[0032] This embodiment provides a method for preparing an ablation-resistant evaporation cooling coating using the self-mass transfer effect of high-speed laser cladding, comprising the following steps:
[0033] 1) Low-melting-point metal surfaces, such as aluminum alloys and copper alloys, have high laser reflectivity. Therefore, the substrate surface needs to be pretreated before high-speed laser cladding experiments. Use low-grit sandpaper to polish the substrate surface to increase its roughness.
[0034] 2) Powder treatment before high-speed laser cladding experiments: The silicon carbide-ultra-high temperature ceramic composite powder is dried in a high-temperature environment to remove moisture and avoid defects such as pores in the coating. When the powder particle size is too fine, the powder beam will shield most of the laser energy, resulting in insufficient melting of the low-melting-point substrate surface, which in turn affects the self-mass transfer effect of the low-melting-point metal into the coating. When the powder particle size is too large, the powder itself will be difficult to melt, resulting in a large number of defects in the coating. Therefore, ceramic powder with a particle size of 45-70 μm is selected by screening.
[0035] 3) The interaction mode between the laser beam and the powder beam determines the energy distribution of the laser beam. Before the high-speed laser cladding experiment begins, the positions of the focal points of the laser beam and the powder beam are adjusted to ensure a reasonable distribution of laser beam energy, so that the low-melting-point metal substrate can reach the coating through the self-mass transfer effect and be uniformly distributed.
[0036] 4) Controlling the process parameters of high-speed laser cladding optimizes coating quality while ensuring the transfer of low-melting-point metal substrate to the coating. The entire high-speed laser cladding experiment was conducted under the protection of a local inert gas atmosphere.
[0037] Specific Implementation Method Four: This implementation method differs from Specific Implementation Method Three in that the material of the low melting point metal matrix in step one is A6061 aluminum alloy, A5052 aluminum alloy, 3003 aluminum alloy, 5083 aluminum alloy, 6063 aluminum alloy, H62 copper alloy, H63 copper alloy, H65 copper alloy, H68 copper alloy, Monel400 copper alloy, or Monel500 copper alloy.
[0038] Specific Implementation Method 5: This implementation method differs from Specific Implementation Methods 3 or 4 in that the ultrasonic power of ultrasonic cleaning is controlled at 150W and the ultrasonic time is 5-10min in step 1.
[0039] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods Three to Five in that the drying time in step two is 30-40 minutes.
[0040] Specific Implementation Method Seven: This implementation method differs from Specific Implementation Methods Three to Six in that the silicon carbide-ultra-high temperature ceramic composite powder in step two is composed of 65-75% wt.% ultra-high temperature ceramic powder and 25-35 wt.% silicon carbide powder.
[0041] Specific Implementation Method Eight: This implementation method differs from Specific Implementation Method Seven in that the ultra-high temperature ceramic powder is ZrB2 ultra-high temperature ceramic powder or TaB2 ultra-high temperature ceramic powder.
[0042] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Methods Three to Eight in that the inert gas in step three is argon gas with a purity of 99.9%.
[0043] Specific Implementation Method 10: This implementation method differs from Specific Implementation Methods 3 to 9 in that in step 3, the laser power is controlled at 2700-3000W, the cladding speed at 100-120mm / s, the powder feeding rate at 2.8-3.2g / min, the overlap rate at 75%-85%, and the spot diameter at 2-3mm.
[0044] Example 1: This example describes a method for preparing an ablation-resistant evaporative cooling coating using the self-mass transfer effect of high-speed laser cladding, implemented according to the following steps:
[0045] 1. Use #240 sandpaper to polish the surface of the 6061 aluminum alloy substrate to be clad for 3 minutes, then immerse the 6061 aluminum alloy substrate in anhydrous ethanol and ultrasonically clean it with a power of 150W for 10 minutes to obtain the cleaned metal substrate.
[0046] 2. Place the silicon carbide-ultra-high temperature ceramic composite powder in a drying oven and dry it at 70°C for 30 minutes to remove the moisture from the powder. After sieving, the silicon carbide-ultra-high temperature ceramic composite powder with a particle size of 45-70μm is obtained.
[0047] 3. The silicon carbide-ultra-high temperature ceramic composite powder is loaded into the powder feeding tank. The focal points of the laser beam and the powder beam are adjusted to coincide below the cladding nozzle. The 6061 aluminum alloy substrate to be clad is placed 1.0 mm below the focal point. The laser power is controlled at 2700 W, the cladding speed is 120 mm / s, the powder feeding rate is 3.0 g / min, the overlap rate is 85%, and the spot diameter is 2 mm. High-speed laser cladding is carried out under the protection of local argon gas. Local argon gas protection means that during the high-speed laser cladding process, the argon gas used to protect the powder beam and the argon gas used to protect the laser beam together surround the molten pool on the substrate surface to prevent the coating from oxidizing. Finally, an ablation-resistant evaporation cooling coating (sample 1) is formed on the surface of the 6061 aluminum alloy substrate.
[0048] The raw materials and equipment used in this embodiment are as follows:
[0049] 1. ZrB2 ultrafine powder was purchased from Nangong Jingrui Alloy Products Co., Ltd., with a particle size of 0.5-1.0μm and a purity of 99.5%.
[0050] 2. The SiC ultrafine powder was purchased from Nangong Jingrui Alloy Products Co., Ltd., with a particle size of 0.5-1.5μm and a purity of 99.5%.
[0051] 3.6061 aluminum alloy was purchased from Taizhou Qianzhan Metal Products Co., Ltd.
[0052] 4. Mix ZrB2 ultrafine powder and SiC ultrafine powder in a mass ratio of 7:3 to form a slurry for spray granulation. Sieve the spray-granulated silicon carbide-ultra-high temperature ceramic composite powder and select powder with a particle size of 45-70μm for high-speed laser cladding.
[0053] 5. The RC-LCD-4000-IPG high-speed laser cladding system was purchased from Nanjing Zhongke Yucheng Laser Technology Co., Ltd.
[0054] Sample 1 for testing the ablation-resistant evaporative cooling coating on the surface of 6061 aluminum alloy:
[0055] The coated aluminum alloy was cut into 18×18×10mm samples using electrical discharge machining. The cross-section of the sample was polished and then the quality of the coating section was observed using an industrial microscope. Figure 1 (a) shows the macroscopic morphology of the coating cross-section. Figure 1 (b) shows the microstructure of the coating cross-section. (From...) Figure 1 (a) and Figure 1 (b) It can be seen that the internal structure of the coating is dense, and the coating-substrate interface is well bonded. For example... Figure 2 (a) and Figure 2 (b) shows the surface morphology of the coating. The coating surface is smooth and free of obvious defects such as cracks. The microstructure and phase composition of the coating were further observed using an electron microscope and a multi-functional X-ray diffractometer to determine whether the coating conforms to the phase structure of an ablation-resistant evaporative cooling coating. Figure 3 (a) is a scanning electron microscope image of the coating cross section. The coating has a dense internal structure and no obvious defects such as pores or cracks. The coating and the substrate exhibit a perfect metallurgical bond. Figure 3 (b) shows the phase analysis results of the coating, which clearly shows that the coating mainly contains ZrB2, SiC, Al and Al. 3.21 Si 0.47 Four phases were observed. No other Zr compounds were found in the coating besides ZrB2, indicating that ZrB2 in the composite ceramic powder was not oxidized or subjected to other chemical reactions during the high-speed laser cladding process and was thus completely preserved. Al and Al2O3 were also found in the coating. 3.21 Si 0.47 The presence of this phase indicates that the self-mass transfer effect of high-speed laser cladding successfully transferred the low-melting-point matrix into the coating. The phase composition of the coating conforms to the pattern of ablation-resistant phases (ZrB2, SiC) + low-melting-point phases (Al, Al). 3.21 Si 0.47 The phase composition of the ablation-resistant evaporative cooling coating.
[0056] The ablation resistance of coating 1 was evaluated using high-energy laser beams with different heat flux densities. The specific parameters of the high-energy laser beams are shown in Table 1.
[0057] Table 1
[0058]
[0059] The surface morphology of the coating before and after ablation with different heat flux densities is as follows: Figure 4 As shown. Figure 4 As shown in (a) and (a1), at 35.39 Mw / m 2 At the given heat flux density, it is difficult to discern a significant difference between the coated surface after ablation and before ablation. This indicates that the coating at 35.39 Mw / m... 2 It exhibits strong ablation resistance at heat flux densities. For example... Figure 4 As shown in (b) and (b1), at 70.77 Mw / m 2 At a heat flux density of 70.77 Mw / m, a noticeable color change appeared on the coating surface, as shown in region A1 of the figure. 2 At a given heat flux density, noticeable ablation marks can be observed on the coating surface, but the surface retains its original morphology, indicating that the heat flux density has not yet reached the ablation threshold of the coating. Figure 4 As shown in (c) and (c1), the A2 region of the coated surface has a strength of 106.16 Mw / m. 2 Obvious ablation pits appeared at the heat flux density of 106.16 Mw / m 2 The heat flux density has reached the ablation threshold of the coating, but the size of the ablation pit is significantly smaller than the size of the laser spot, indicating that the coating exhibits incomplete ablation at this heat flux density. Figure 4 (d) and (d1) represent the coating at 141.54 Mw / m 2 The morphology before and after heat flux density ablation is shown. It is evident that the size of the ablation pit in region A3 of the coating is close to the size of the laser beam, indicating that the coating underwent relatively complete ablation at this heat flux density. In summary, the ablation-resistant evaporative cooling coating prepared by high-speed laser cladding exhibits a high ablation threshold and excellent ablation resistance under high-energy laser beam ablation.
[0060] Example 2: This example describes a method for preparing an ablation-resistant evaporative cooling coating using the self-mass transfer effect of high-speed laser cladding, implemented according to the following steps:
[0061] 1. Use #240 sandpaper to polish the surface of the 6061 aluminum alloy substrate to be clad for 3 minutes, then immerse the 6061 aluminum alloy substrate in anhydrous ethanol and ultrasonically clean it with a power of 150W for 10 minutes to obtain the cleaned metal substrate.
[0062] 2. Place the silicon carbide-ultra-high temperature ceramic composite powder in a drying oven and dry it at 70°C for 30 minutes. After sieving, the silicon carbide-ultra-high temperature ceramic composite powder with a particle size of 45-70μm is obtained.
[0063] 3. The silicon carbide-ultra-high temperature ceramic composite powder is loaded into the powder feeding tank. The focal points of the laser beam and the powder beam are adjusted to coincide below the cladding nozzle. The surface of the 6061 aluminum alloy substrate to be clad is placed 1.0 mm below the focal point. The laser power is controlled at 2200 W, the cladding speed is 120 mm / s, the powder feeding rate is 3.0 g / min, the overlap rate is 85%, and the spot diameter is 2 mm. High-speed laser cladding is carried out under the protection of local inert gas to form an ablation-resistant evaporation cooling coating on the surface of the 6061 aluminum alloy substrate (sample 2).
[0064] Sample 2, for testing the ablation-resistant evaporative cooling coating on the surface of 6061 aluminum alloy:
[0065] After cladding, the coated aluminum alloy was cut into 18×18×10mm samples using electrical discharge machining. The cross-section of the sample was then polished and the quality of the coating section was observed using an industrial microscope. Figure 5 (a) shows the macroscopic morphology of the coating cross-section. Figure 5 (b) shows the microstructure of the coating cross-section. (From...) Figure 5 (a) and Figure 5 (b) It can be seen that the coating exhibits obvious peeling. This proves that when the laser power decreases, the output energy of the laser beam is lower, and the silicon carbide-ultra-high temperature ceramic composite powder cannot be fully melted, leading to coating peeling. The coating defects in this embodiment are quite obvious and can no longer meet the actual engineering needs; therefore, further ablation tests were not conducted.
[0066] Example 3: This example describes a method for preparing an ablation-resistant evaporative cooling coating using the self-mass transfer effect of high-speed laser cladding, implemented according to the following steps:
[0067] 1. Use #240 sandpaper to polish the surface of the 6061 aluminum alloy substrate to be clad for 3 minutes, then immerse the 6061 aluminum alloy substrate in anhydrous ethanol and ultrasonically clean it with a power of 150W for 10 minutes to obtain the cleaned metal substrate.
[0068] 2. Place the silicon carbide-ultra-high temperature ceramic composite powder in a drying oven and dry it at 70°C for 30 minutes. After sieving, the silicon carbide-ultra-high temperature ceramic composite powder with a particle size of 45-70μm is obtained.
[0069] 3. The silicon carbide-ultra-high temperature ceramic composite powder is loaded into the powder feeding tank. The focal points of the laser beam and the powder beam are adjusted to coincide below the cladding nozzle. The surface of the 6061 aluminum alloy substrate to be clad is placed 1.0 mm below the focal point. The laser power is controlled at 2700 W, the cladding speed is 160 mm / s, the powder feeding rate is 3.0 g / min, the overlap rate is 85%, and the spot diameter is 2 mm. High-speed laser cladding is carried out under the protection of local inert gas to form an ablation-resistant evaporation cooling coating on the surface of the 6061 aluminum alloy substrate (sample 3).
[0070] Sample 3, for testing the ablation-resistant evaporation cooling coating on the surface of 6061 aluminum alloy:
[0071] After cladding, the coated aluminum alloy was cut into 18×18×10mm samples using electrical discharge machining. The cross-section of the sample was then polished and the quality of the coating section was observed using an industrial microscope. Figure 6 (a) shows the macroscopic morphology of the coating cross-section. Figure 6 (b) shows the microstructure of the coating cross-section. (From...) Figure 6 (a) and Figure 6 (b) It can be seen that there are obvious pores in the coating-substrate interface. This proves that as the cladding speed increases, the interaction time between the laser beam and the aluminum alloy surface decreases, and the aluminum alloy surface cannot be fully melted, resulting in a large number of pores on the coating-substrate surface. The coating defects in this embodiment are quite obvious and can no longer meet the actual engineering requirements; therefore, no further ablation tests were conducted.
[0072] In summary, this invention provides a method for preparing an ablation-resistant evaporative cooling coating for a low-melting-point metal surface. Within the scope defined by this invention, a coating with good quality and excellent ablation resistance can be obtained. When the laser power exceeds the limits defined by this invention, insufficient melting of the silicon carbide-ultra-high temperature ceramic composite powder will occur, leading to coating detachment. When the cladding speed exceeds the limits defined by this invention, the interaction time between the laser beam and the substrate will be shortened, resulting in a large number of pores at the coating-substrate interface. These obvious defects pose significant risks during coating service, easily deteriorating the coating's ablation resistance and causing premature coating failure. Within the process scope defined by this invention, a high-quality ablation-resistant evaporative cooling coating can be obtained.
[0073] The method for preparing ablation-resistant evaporative cooling coatings using the self-mass transfer effect of high-speed laser cladding provided by this invention mainly addresses the shortcomings of current ablation-resistant coating methods. It employs high-speed laser cladding technology and utilizes the self-mass transfer effect to introduce a low-melting-point metal into the coating, thus completing the preparation of the ablation-resistant evaporative cooling coating. The coating mainly consists of an ablation-resistant phase derived from the original powder, and an evaporative cooling phase derived from the low-melting-point metal matrix. The low-melting-point metal is transferred into the coating through the self-mass transfer effect of high-speed laser cladding. This method can prepare coatings of high quality with excellent ablation resistance, effectively solving the problems existing in current ablation-resistant coatings.
Claims
1. An ablation-resistant evaporative cooling coating, characterized in that... The ablation-resistant evaporative cooling coating is prepared using a high-speed laser cladding process. The cladding nozzle sprays silicon carbide-ultra-high temperature ceramic composite powder, and the laser beam simultaneously irradiates the silicon carbide-ultra-high temperature ceramic composite powder and the surface of a low-melting-point metal substrate. A coating containing an ablation-resistant phase and an evaporative cooling phase is formed on the surface of the low-melting-point metal substrate. The ablation-resistant phase is the silicon carbide-ultra-high temperature ceramic composite material, and the evaporative cooling phase is the metal phase of the low-melting-point metal that is transferred to the coating through a complete self-mass transfer effect. The material of the low-melting-point metal substrate is an aluminum alloy or a copper alloy.
2. The ablation-resistant evaporative cooling coating according to claim 1, characterized in that... The coating thickness formed on the surface of a low-melting-point metal substrate is 300-450 μm.
3. A method for preparing an ablation-resistant evaporative cooling coating using the self-mass transfer effect of high-speed laser cladding, characterized in that... The method for preparing an ablation-resistant evaporative cooling coating is carried out according to the following steps:
1. Use #240~#300 sandpaper to polish the surface of the low melting point metal substrate, and then immerse the low melting point metal substrate in anhydrous ethanol for ultrasonic cleaning to obtain the cleaned metal substrate.
2. Place the silicon carbide-ultra-high temperature ceramic composite powder in a drying oven and dry it at a temperature of 60-100℃. After sieving, the silicon carbide-ultra-high temperature ceramic composite powder with a particle size of 45-70μm is obtained.
3. Load silicon carbide-ultra-high temperature ceramic composite powder into a powder feeding tank, adjust the focal points of the laser beam and the powder beam to coincide below the cladding nozzle, place the metal substrate surface to be clad 0.5-1.2 mm below the focal point, control the laser power to be 2300-3300 W, the cladding speed to be 90-150 mm / s, the powder feeding rate to be 2.8-3.4 g / min, the overlap rate to be 75%-90%, and the spot diameter to be 2-3 mm. Perform high-speed laser cladding under the protection of local inert gas to form an ablation-resistant evaporation cooling coating on the surface of the low melting point metal substrate. The low-melting-point metal matrix is made of aluminum alloy or copper alloy.
4. The method for preparing an ablation-resistant evaporative cooling coating using the self-mass transfer effect of high-speed laser cladding according to claim 3, characterized in that... In step one, the material of the low-melting-point metal matrix is A6061 aluminum alloy, A5052 aluminum alloy, 3003 aluminum alloy, 5083 aluminum alloy, 6063 aluminum alloy, H62 copper alloy, H63 copper alloy, H65 copper alloy, H68 copper alloy, Monel400 copper alloy, or Monel500 copper alloy.
5. The method for preparing an ablation-resistant evaporative cooling coating using the self-mass transfer effect of high-speed laser cladding according to claim 3, characterized in that... In step one, the ultrasonic power of the ultrasonic cleaning is controlled at 150W, and the ultrasonic time is 5-10 minutes.
6. The method for preparing an ablation-resistant evaporative cooling coating using the self-mass transfer effect of high-speed laser cladding according to claim 3, characterized in that... The drying time in step two is 30-40 minutes.
7. The method for preparing an ablation-resistant evaporative cooling coating using the self-mass transfer effect of high-speed laser cladding according to claim 3, characterized in that... In step two, the silicon carbide-ultra-high temperature ceramic composite powder is composed of 65-75% wt.% ultra-high temperature ceramic powder and 25-35 wt.% silicon carbide powder.
8. The method for preparing an ablation-resistant evaporative cooling coating using the self-mass transfer effect of high-speed laser cladding according to claim 7, characterized in that... The ultra-high temperature ceramic powder is either ZrB2 ultra-high temperature ceramic powder or TaB2 ultra-high temperature ceramic powder.
9. The method for preparing an ablation-resistant evaporative cooling coating using the self-mass transfer effect of high-speed laser cladding according to claim 3, characterized in that... The inert gas in step three is argon with a purity of 99.9%.
10. The method for preparing an ablation-resistant evaporative cooling coating using the self-mass transfer effect of high-speed laser cladding according to claim 3, characterized in that... In step three, the laser power is controlled at 2700-3000 W, the cladding speed at 100-120 mm / s, the powder feeding rate at 2.8-3.2 g / min, the overlap rate at 75%-85%, and the spot diameter at 2-3 mm.
Citation Information
Patent Citations
Preparation method of zirconium boride-zirconium carbide-silicon carbide composite coating
CN111334743A
Method for preparing ceramic-based composite coating by adopting high-speed laser cladding process
CN116479417A